Solving Parallel Multi Component Automata Equations - Shabaldina, N.; Yevtushenko, N. (ХНУРЭ, 2008)
The problem of designing the unknown component of a system of interacting automata that combined with the known part of the system meets the specification, is well known. However, most publications are devoted to solving the problem for the proper composition of two automata. In this paper, we consider a parallel multi component automata equation and propose two methods for deriving a largest solution to this equation (if the equation is solvable). In particular, we show that the union of alphabets over all known components and of that of the specification is the largest alphabet of actions over which a solution for a solvable equation should exist, and show how a solution over an appropriate alphabet can be derived from such a largest solution.
Keywords: discrete event systems; equations; automata